L'educatore professionale socio-pedagogico nei servizi educativi e scolastici tra sviluppo sostenibile e governance inclusiva: alcuni dati di ricerca - Lucia Chiappetta Cajola; Marianna Traversetti (LED Edizioni Universitarie, 2018)
The study proposes some reflections about the professional profile of the socio-pedagogical educator in the framework of inclusive education. In Italy, also in the perspective of the long life learning, the 205/2017 law attributes a fundamental role to the educator in connection with the dialogue, the collaboration and the interaction between the professional community and the school service. As observed by some ICF-CY based research (the ICF-CY application has recently been underlined also in the formative field), the educator is a link between school, children, students and families. He gives a very important contribute to realize the «Plan of education for sustainability» and the governance of special educational needs, enhancing formal, informal and non-formal learning. The educator can contribute to constructing innovative practices and reflective transformation by deepening and research: this is an identifying element of inclusive governance. In this context, the educator is an engine of effective relationship and mediation between school and territory and he establishes himself as a professional able to act in the dialectic and constructive relationship with all the subjects who work in educational services.